Digital mammography : a practical approach - Haygood, Tamara Miner , 1956-; Whitman, Gary J. (Cambridge medicine, 2013)
"Digital mammography has many advantages over film-screen mammography, including faster acquisition, easier storage and easier retrieval of images. Written by expert radiologists and physicists, Digital Mammography: A Practical Approach compares digital mammography to conventional film-screen mammography, reviews clinical cases and explores newer modalities. Key topics include: Digital detectors ; Monitors ; Image acquisition ; Image storage, retrieval and transfer ; Image interpretation and efficacy ; Artifacts ; A comparison of commercially available systems ; Mobile digital mammography. An image atlas and sections on digital tomosynthesis and computed tomography of the breast enhance the text. Digital Mammography: A Practical Approach melds the worlds of clinical radiology and physics in an easy-to-understand, practical resource. A valuable addition to the shelf of radiologists, radiologic technicians, practising medical physicists and mammography technologists; and any practitioners developing and expanding digital mammography programs." -- Publisher's website